Use of parabolic trough solar energy collectors for sea-water desalination - Kalogirou, Soteris A. (My University, 1998)
The various desalination methods are analysed with respect to their primary energy consumption, sea-water treatment requirement and equipment cost. From this analysis, the multiple-effect boiling evaporator is concluded to be the most suitable method for stimulation by solar energy. The parabolic-trough solar-collector is selected mainly due to its ability to function at high temperatures with high efficiency. The design of the flash vessel and the desalination system circuit are presented. System modelling is used to predict the rate of fresh water produced by four sizes of systems, varying from small 10 m2 to large 2160 m2 collector-area applications. The economic analysis performed, showed that prices of about 0.89 C£/m2 can be achieved with the larger applications. Nevertheless, it is not cost effective to operate the system solely on solar energy due to the relatively high cost of the equipment and the high percentage of inactive time.
Keywords: Solar collectors; Desalination; Seawater; Evaporators; Mathematical models; Systems analysis; Economics; Cost benefit analysis; Cost effectiveness; Parabolic through solar energy collectors; Multiple effect boiling evaporator; System modelling; Economic analysis; Thermal efficiency; Optical efficiency